2014
DOI: 10.1186/1750-1172-9-77
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune pancreatitis can develop into chronic pancreatitis

Abstract: Autoimmune pancreatitis (AIP) has been recognized as a distinct type of pancreatitis that is possibly caused by autoimmune mechanisms. AIP is characterized by high serum IgG4 and IgG4-positive plasma cell infiltration in affected pancreatic tissue. Acute phase AIP responds favorably to corticosteroid therapy and results in the amelioration of clinical findings. However, the long-term prognosis and outcome of AIP remain unclear. We have proposed a working hypothesis that AIP can develop into ordinary chronic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 52 publications
0
29
0
4
Order By: Relevance
“…Conversely, while autoimmune pancreatitis is an AID suggested to develop into chronic pancreatitis, its link with PC risk has not been established . Moreover, it is reasonable to expect a different type of association in AIDs that result in localized damage to the pancreas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, while autoimmune pancreatitis is an AID suggested to develop into chronic pancreatitis, its link with PC risk has not been established . Moreover, it is reasonable to expect a different type of association in AIDs that result in localized damage to the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…44 Conversely, while autoimmune pancreatitis is an AID suggested to develop into chronic pancreatitis, its link with PC risk has not been established. 45,46 Moreover, it is reasonable to expect a different type of association in AIDs that result in localized damage to the pancreas. Moreover, one could hypothesize that the decreased risk of certain cancers and AIDs could be the consequence of confounding by particular treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, the response to glucocorticoids has been evaluated by means of identifying radiological abnormalities such as tumefactive or hyperplastic lesions, the clinical symptoms caused by them, and functional parameters of the affected organs, including renal function [8, 10], salivary secretory function [18], and pancreatic exocrine and endocrine function [19, 20]. Numerous reports reveal that these indicators improve at least initially after the initiation of glucocorticoid therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Transformation into chronic pancreatitis associated with pancreatic stones, atrophy, and exocrine and endocrine dysfunction has been reported in the long-term clinical course of type 1 AIP [19, 20]. A study investigating the long-term clinical course in IgG4-RKD showed that patients with pre-treatment eGFR under 60 mL/min/1.73 m 2 calculated on the basis of the Japanese revised equation for estimating GFR from serum creatinine [22] attained not complete but only partial recovery of renal function one month after the start of glucocorticoid therapy, with residual dysfunction persisting thereafter, and that radiologically, focal or diffuse renal atrophy persisted [8].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous factors have been implicated for causation and association of pancreatitis ranging from exogenous elements including lifestyle and behaviour like alcohol [13][14][15] , smoking, tobacco consumption [15,16] , nutrition, diet [17,18] , environmental toxins, geography [19] to endogenous elements like gallstones [1,12,20] , genetics [21] , autoimmunity [22] ,etc.…”
mentioning
confidence: 99%